1999
DOI: 10.1002/(sici)1096-9861(19990510)407:3<318::aid-cne2>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Projections of the vestibular nuclei to the thalamus in the rat: A Phaseolus vulgaris leucoagglutinin study

Abstract: Injections of the anterograde axonal tracer Phaseolus vulgaris leucoagglutinin were made into individual nuclei of the vestibular nuclear complex of the rat to identify specific projections to the thalamus. The results showed that the superior vestibular nucleus and the medial vestibular nucleus, especially its rostral-to-middle parts, project to the lateral part of the parafascicular thalamic nucleus (corresponding to the centromedian nucleus in primates), the transitional zone between the ventrolateral thala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 79 publications
6
72
1
1
Order By: Relevance
“…Consequently, we hypothesized that either primate vestibular nuclei inputs are actually more broadly distributed, like those of rodents (Nagata, 1986;Shiroyama et al, 1999), or that the thalamus might receive vestibular information from areas other than the VN. Because vestibular signals in VPL presumably originate from its VN input , we aimed an injection at a region dorsal to VPL to retrogradely label its inputs.…”
Section: Vestibulocerebellothalamic Projectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, we hypothesized that either primate vestibular nuclei inputs are actually more broadly distributed, like those of rodents (Nagata, 1986;Shiroyama et al, 1999), or that the thalamus might receive vestibular information from areas other than the VN. Because vestibular signals in VPL presumably originate from its VN input , we aimed an injection at a region dorsal to VPL to retrogradely label its inputs.…”
Section: Vestibulocerebellothalamic Projectionsmentioning
confidence: 99%
“…Widespread, bilateral thalamic projections from the vestibular nuclei (VN) have been reported in the rat (Nagata, 1986;Shiroyama et al, 1995Shiroyama et al, , 1999 and cat (Kotchabhakdi et al, 1980;Maciewicz et al, 1982;Nakano et al, 1985). However, the projection in primates appears to be more discrete.…”
Section: Introductionmentioning
confidence: 99%
“…These thalamic areas project to the frontal cortex including FEF (Shiroyama et al 1999). Ebata et al (2004, using the laminar field potential analysis, suggested that vestibular-evoked potentials in the caudal FEF of monkeys were directly conveyed to the cortex through the thalamus, consistent with the anatomical studies (Shiroyama et al 1999).…”
Section: Vestibular Signals In the Caudal Fefmentioning
confidence: 99%
“…The efferent and afferent connections of the vestibular nuclei were important and were therefore intensively studied in rat [42], squirrel monkey [43,44], cat, and monkey [45,46]. Spinocerebellar afferents were studied in the rat, cat, and squirrel monkey [47], as well as the otolith pathways [48].…”
Section: Anatomy Of Vestibular Systemmentioning
confidence: 99%
“…Coerulovestibular pathways were also studied in rats, rabbits, and monkeys [49]. Figure 1 demonstrates the essence of the innervation focused on the vestibular nuclei [42].…”
Section: Anatomy Of Vestibular Systemmentioning
confidence: 99%